Lactate and cancer: a “lactatic” perspective on spinal tumor metabolism (part 1) - Goodwin, Matthew L. (Ann Transl Med, 2019)
Spine tumors are among the most difficult tumors to treat given their proximity to the spinal cord. Despite advances in adjuvant therapies, surgery remains a critical component of treatment, both in primary tumors and metastatic disease. Given the significant morbidity of these surgeries and with other current adjuvant therapies (e.g., radiation, chemotherapy), interest has grown in other methods of targeting tumors of the spine. Recent efforts have highlighted the tumor microenvironment, and specifically lactate, as central to tumorigenesis. Once erroneously considered a waste product that indicated hypoxia/hypoperfusion, lactate is now known to be at the center of whole-body metabolism, shuttling between tissues and being used as a fuel. Diffusion-driven transporters and the near-equilibrium enzyme lactate dehydrogenase (LDH) allow rapid mobilization of large stores of muscle glycogen in the form of lactate. In times of stress, catecholamines can bind muscle cell receptors and trigger the breakdown of glycogen to lactate, which can then diffuse out into circulation and be used as a fuel where needed. Hypoxia, in contrast, is rarely the reason for an elevated arterial [lactate]. Tumors were originally described in the 1920’s as being “glucose-avid” and “lactate-producing” even in normoxia (the “Warburg effect”). We now know that a broad range of metabolic behaviors likely exist, including cancer cells that consume lactate as a fuel, others that may produce it, and still others that may change their behavior based on the local microenvironment. In this review we will examine the relationship between lactate and tumor metabolism with a brief look at spine-specific tumors. Lactate is a valuable fuel and potent signaling molecule that has now been implicated in multiple steps in tumorigenesis [e.g., driving vascular endothelial growth factor (VEGF) expression in normoxia]. Future work should utilize translational animal models to target tumors by altering the local tumor microenvironment, of which lactate is a critical part.